Compact UWB bandpass filter with high suppression at 2.4 and 5.8 GHz - Law, Choi Look (2013)
A circuit model is proposed for the design of an ultra-wideband (UWB) bandpass filter (BPF) with high out-of-band suppression at two different frequencies. Based on theoretical analysis and numerical simulation of this proposed circuit model, an UWB BPF is fabricated and measured for verification. This fabricated filter has a measured 3 dB passband of 3–4.5 GHz, with a compact size of only 10 × 9.8 mm. Moreover, it has a high rejection of 40 dB at 2.4 GHz, and 30 dB at 5.8 GHz, respectively. This UWB BPF is useful to alleviate the strong WLAN signals interference to UWB receivers.